The Influence of Human Resource Quality on Employee Performance with Job Satisfaction as an Intervening Variable at Bank Sumut Binjai Branch - Suhardiman Suhardiman; Kiki Farida Ferine (International Journal of Economics, Management and Accounting (IJEMA), 2023)
The purpose of this study was to analyze the influence of human resource quality on employee performance with job satisfaction as an intervening variable. This research was conducted at Bank Sumut Binjai Branch. The population of this study was 70 employees and the sample used was 70 employees (sample saturated). Data collection was carried out by distributing questionnaires. The research model used is Path analysis. The result of this study is that Job Satisfaction has no significant positive effect on Employee Performance. HR quality has a positive and significant effect on job satisfaction. HR quality has a positive and insignificant effect on employee performance. Based on this study, there is a positive and significant effect of HR quality on Employee Performance through Job Satisfaction.